(3eNJUQ cJGH GdMjhGfs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s ((3eMeO Hf ehSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CaGV Ydi gPG GdhLhO hHYO agPG eG jMSf Ydjg GdEbJUGQ GdeTJed Ydjg cJGH MjGI GdMjhGf ddYdGeI GdEeGe GdOejQi HGH MQa GdCda s
(3BNQgG (B:s
(3Gddge CSJQfi ai faSi hOjfi hUdi Gddg Ydi SjOfG eMeO NGJe GdfHjjf hYdi Bdg hCUMGHg CLeYjf GfJgi eG hLO HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B65 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B178s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(251) s
Keywords: (3GdeLGejYs